2013
DOI: 10.1007/s11894-013-0370-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fructose Intolerance, Fructan Intolerance and FODMAPs

Abstract: Dietary intolerances to fructose, fructans and FODMAPs (Fermentable Oligosaccharides, Disaccharides, Monosaccharides And Polyols) are common, yet poorly recognized and managed. Over the last decade, they have come to the forefront because of new knowledge on the mechanisms and treatment of these conditions. Patients with these problems often present with unexplained bloating, belching, distension, gas, abdominal pain or diarrhea. Here, we have examined the most up-to-date research on these food-related intoler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
102
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 36 publications
(56 reference statements)
1
102
0
8
Order By: Relevance
“…59 A low FODMAP diet seemed beneficial in adult IBS trials, but due to heterogeneity in study design and outcomes and because of unknown long-term safety and efficacy, definitive conclusions cannot be drawn. 60 Recently, a randomized, double-blind, crossover trial in 33 children with IBS reported improvement in abdominal pain after receiving a 48-hour low FODMAP diet. 61 Although these results seem promising, more longterm studies are needed to further assess the efficacy and safety of a low FODMAP diet in children and adolescents.…”
Section: Alternative Medicinementioning
confidence: 99%
“…59 A low FODMAP diet seemed beneficial in adult IBS trials, but due to heterogeneity in study design and outcomes and because of unknown long-term safety and efficacy, definitive conclusions cannot be drawn. 60 Recently, a randomized, double-blind, crossover trial in 33 children with IBS reported improvement in abdominal pain after receiving a 48-hour low FODMAP diet. 61 Although these results seem promising, more longterm studies are needed to further assess the efficacy and safety of a low FODMAP diet in children and adolescents.…”
Section: Alternative Medicinementioning
confidence: 99%
“…Fructose malabsorption has been reported with ingestion above tolerance levels (Ebert andWitt 2016, Fedewa andRao 2014). However, the adjunct ingestion of glucose with fructose appears to lower the malabsorption rate in response to a fructose challenge in a resting state (Truswell et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are catching researchers' attention for their health-promoting effects, to the point that they are gradually being added to a wider variety of food products as fortification agents, and are being increasingly used as the main components in dietary supplements [28,41]. However, recent researches have emphasized that particular attention must be paid to consumers with problems of dietary intolerances to fructans and fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAPs) [42].…”
Section: Introductionmentioning
confidence: 99%